Phosphorylation of S‐S‐S Motif in Nuclear Export Protein (NEP) Plays a Critical Role in Viral Ribonucleoprotein (vRNP) Nuclear Export of Influenza A and B Viruses - Xiaokun Liu; Cha Yang; Xian Lin; Xiaomei Sun; Huanchun Chen; Qiang Zhang; Meilin Jin (Advanced Science)
Abstract The phosphorylation of three highly conserved serine residues S23, S24, and S25 (S‐S‐S motif) has been previously identified in NEP of influenza virus. However, it remains obscure whether and how this motif regulates the vRNPs nuclear export. Here the influenza A H5N6 viruses harboring NEP S23C, S24L, or S25L is generated, allowing to impair the phosphorylation on these sites without mutating viral NS1 protein. These mutations significantly inhibited vRNPs nuclear export are founded, decreased viral infectivity and attenuated virulence in mice. In addition, inhibition or knockout of ATM or CK2, two predicated Ser/Thr protein kinases that phosphorylate the S‐S‐S motif, impedes vRNP nuclear export and virus replication in cells and reduces the virulence in vivo. Moreover, treatment of NEP peptide mimics containing the S‐S‐S motif to competitively block NEP binding to the kinases reduces influenza virus replication in cells and mice. However, neither the inhibitors above nor the NEP peptide mimics significantly inhibit the replication of H5N6‐DDD mutant, indicating phosphorylation of S‐S‐S motif is required for the vRNP nuclear export. This studies contribute to a better understanding of the mechanism by which NEP regulates vRNP nuclear export and provides novel insights into antiviral targets against influenza A and B viruses.